SISTEM KEAMANAN RUMAH BERBASIS MIKROKONTROLER ARDUINO DAN ANDROID - Mukhtar, Sigit Adi; Pontoiyo, Fuad (Program Vokasi Universitas Negeri Gorontalo, 2024)
Housing development in Gorontalo City is targeted merely to meet the need for a home but has no security concerns for the homeowners; even some houses are not equipped with security guards, making fires and thefts possible to occur. Considering the issues, we propose the application of an Arduino and Android microcontroller-based security system using Wemos D1 as a smartphone communication intermediary with devices integrated into the system using an MQ2 gas sensor, PIR (Passive Infrared) motion sensor, water level sensor, DHT11 temperature sensor, face recognition with ESP32cam, RFID as a replacement for door locks, and light control using relays. Our product allows users to control home devices and monitor any activities inside their homes remotely. Notifications will be sent if any sign of fire is detected, and an option to call on firefighters if the fire point is identifiable will be offered. In the case of an encounter with criminal acts, users will be sent a screenshot of the intruders and offered an option to file reports to the police.